Some effects of cimetidine on the reproductive organs of rats - Pereira, O. C. M. (Elsevier B.V., 1987)
1. The development of genital organs of rats chronically treated with cimetidine showed that the drug may present anti-androgenic activity. 2. This treatment did not alter the sensitivity of vas deferens to noradrenaline, but increased their sensitivity to BaCl2. 3. In the male reproductive system, cimetidine must have peripheral actions apart from the central ones observed after chronic treatment.
Keywords: Barium; Cimetidine; Cocaine; Lenarterenol; Noradrenalin; Unclassified drug; Animal cell; Animal experiment; Genital system; Intraperitoneal drug administration; Male genital system; Nonhuman; Priority journal; Rat; Vas deferens; Animal; Barium; Cimetidine; Genitalia, Male; Male; Norepinephrine; Organ Weight; Pituitary Gland; Prostate; Rats; Rats, Inbred Strains; Seminal Vesicles; Testis; Vas Deferens